Photography's Other Histories - Peterson, Nicolas; Pinney, Christopher (Book collections on Project MUSE., 2003)
A collection seeking to rethink photography as a globally disseminated and locally appropriated medium, rather than as one advanced almost exclusively through Western technology and singular photographers.